REGIONAL MAPPING IN BANGKALAN DISTRICT BASED ON POTENTIAL INDICATORS OF TOTAL STUNTING USING K-MODE CLUSTER ALGORITHM - Adma Novita Sari; Dzuria Hilma Qurotu’ain; Faradilla Harianto; Sa'idah Zahrotul Jannah (Media Gizi Indonesia, 2022)
Indonesia has the highest number of stunted children in Southeast Asia. Indonesia's stunting prevalence rate is also still higher than the threshold set by WHO (20%). This issue has become a particular concern of the government. Hence, by 2024, the government targets the prevalence of stunting to decrease to 14% under Presidential Regulation no. 72 of 2021. One of the highest stunting cases in Indonesia is Bangkalan Regency, which has a prevalence rate of 38.9%, exceeding the maximum stunting target limit in Indonesia. Therefore, this study aimed to map the area in Bangkalan Regency based on the factors that influence stunting cases in toddlers. This study used data from the National Population and Family Planning Agency (BKKBN) survey in 2021. The results show that several sub-districts in Bangkalan still have poor water availability, sanitation, environmental hygiene, and housing welfare. Mapping the area can help the government provide the right solution for the area's problems.